(3TQM eZfi GddHjHs - (3YHO Gddg Hf jhSa Hf CMeO GdCfUGQj GdeUQj GdfMhj , LeGd GdOjf , CHh eMeO, GHf gTGe J (B761 (3g` s
(3ChdgG (B:s
(3ef GdKbjdI hjdRe ef GdEYeGd chfgG eNaaI , abO JVef GdOdjd QO Gdbhd HCfgG GdfGajI s
(3BNQgG (B:s
(3hGdMeO ddg Ydi fYeg GdYXGe heffg GdLSGe , hfSCdg MSjf GdNJGe , hGdacGc ef QHbI GdBKGe , hCf jMTQfG ai ReQI fHjfG eMeO Ydjg CaVd GdUdGI hGdSdGe hYdi Bdg hGUMGHg GdSGOI GdcQGe s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdfMhs